IDENTIFIKASI DAN MITIGASI RISIKO STRATEJIK MENGGUNAKAN IFE-EFE MATRIX: STUDI KASUS BPJS KESEHATAN - Hanggraeni, Dewi; Triana, Dea R.; Kuswanto, Luna S.; Alfarisi, M. Iqbal; Rahayu, Renata H. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
This study identifies and analyzes strategic risks experienced by the Badan Pengelola Jaminan Sosial (BPJS) Kesehatan. This health insurance program has a deficit due to the number of claims exceeding income and there is no detection system for the number of claims that are not appropriate. This research is explanatory by using the IFE-EFE Matrix as a basis for identifying and mitigating the strategic risk of BPJS Kesehatan. The Analysis results shows the need for more accurate and transparent calculations, intense socialization, pricing of tariff should be adjusted to the ability of the people, as well as a fraud detection system by BPJS Kesehatan.Keywords: Strategic Risk; IFE and EFE Matrix; BPJS Kesehatan, UCS Thailand